Physico-chemical parameters of surface water and preliminary health risk assessment studies of Paka and Kerteh River - Fazureen Azaman
In Malaysia, the problem of water pollution has become the major problem toward the economic growth of the country nowadays. Mostly people or private company chooses river as a dumping site to discharge their waste directly or indirectly into the river. This study is specifically concerned with the river water quality status, including metal concentration and their potential health risk towards human. The empirical part of this study was conducted in Kerteh and Paka Rivers during wet and dry season. In situ sampling had been done by collecting some parameter such as pH, total dissolved solid (TDS), dissolved oxygen (DO), ammonical nitrogen (NH4 "N), nitrate nitrogen (NO) -N), conductivity and salinity using handheld multi-probe meter, while turbidity using turbidimeter. For ex-situ sampling, 108 water samples were collected and analyzed using inductively coupled plasma optical emission spectrometry (ICP-OES) for metal determination (nickel (Ni), lead (Pb), copper (Cu), cadmium (Cd), chromium (Cr), zinc (Zn), cobalt (Co) and arsenic (As». The analysis from this study was perfonned using various methods from descriptive and multivariate analysis. In descriptive analysi , the results revealed that most of the sampling point in the Kerteh River gave the higher concentration on turbidity, DO, pH, TDS, conductivity, salinity, NH4-N, NO)"N, Cd, Cu, Zn, Co, Ni, As, Cr and Pb compared to the Paka River as well as higher concentration during wet season rather than dry season. Besides, the result of multivariate analysis done by principal component analysis (PCA) and partial least squares discriminant analysis (PLS-DA) indicated that the main sources of river water pollution could be related to point sources pollution such as industry waste (heavy metal, oil and petrochemical pollution) and domestic wastewater and also non-point Sources pollution such as agricultural activities, geologic deposits and organic. PCA and PLS-DA gave good distribution and clustering among sampling point and water quality parameter. However, clustering of PLS-DA gave a better compared to the PCA through the biplot graph given. Moreover, preliminary risk assessments via hazard quotient through dermal (HQdennal) to children and adult, resulted from Cr, the levels were higher than the acceptable levels (HQ > I) depends on the stations and seasons. There is no non-cancer risk in all metals for hazard quotient through ingestion (HQingcstion) for both age groups in the both rivers, including wet and dry season. The cancinogenic risk via dermal (C~ennal) posed by As were higher than the acceptable level « 1.0 x I 0-4) for station S6, S7, S8 and S9 of Kerteh and Paka Rivers during both season, including adult and child. However, the results illustrated that the carcinogenic risk through the ingestion exposure pathway (CRingcstion) was mainly attributed to As and Cr which had carcinogenic risk levels that were higher than < 1.0 x 10-4 in almost every sampling point in the both rivers and seasons, followed by Cd that mo tly happen only in the downstream of the river. The water from contaminated sites should not be used for drinking without proper treatment. The proper action must be taken immediately to ensure the safety of water consumption towards human health.